Clinical learning environments and experiences of nursing students in West Bank Universities: A mixed-methods study - Nihad Bsharat; Ibrahim Aqtam; Hanan Al-Modallal; Mutaz Dreidi; Mustafa Shouli (PLoS ONE, 2025)
Background Clinical learning environments (CLEs) play a vital role in shaping nursing students’ competencies, yet their dynamics in conflict-affected settings remain underexplored. This study investigated how CLE factors, measured via the Clinical Learning Environment, Supervision and Nurse Teacher (CLES+T) scale, relate to students’ clinical learning (CL) experiences across West Bank universities in Palestine. The findings are specific to the Palestinian context but may offer insights for other conflict-affected educational settings. Methods A convergent mixed-methods design integrated quantitative data from 306 nursing students across governmental, public, and private universities with qualitative insights from 14 in-depth interviews. The validated Arabic CLES+T scale, culturally adapted for the Palestinian context, assessed five CLE dimensions. Quantitative analysis included ANOVA, correlation, and hierarchical multiple regression. Assumptions for parametric tests (normality, multicollinearity, and homoscedasticity) were verified before conducting ANOVA and regression analyses. Qualitative data underwent inductive content analysis with dual coding by two independent researchers to ensure reliability. Results CLE dimensions were strongly correlated with students’ clinical learning experiences (r = 0.758, p < 0.001). Pedagogical atmosphere (β = 0.365, p < 0.001) and supervisory relationships (β = 0.264, p = 0.001) were significant predictors, jointly explaining 59% of the variance (R² = 0.59). Students reported more positive CL experiences in governmental hospitals (M = 3.92 ± 0.91) compared to private facilities (M = 3.59 ± 1.06, p = 0.032). Significant differences emerged across clinical wards (F[6,299]=2.56, p = 0.019), with orthopedic wards receiving the highest scores and pediatric wards the lowest. Qualitative findings highlighted four themes: students’ perceptions of clinical experiences, key facilitators (e.g., instructor expertise), barriers (e.g., movement restrictions, limited resources), and strategies for improvement (e.g., expanding clinical exposure and diversifying placement sites). Conclusion In the conflict-affected Palestinian context, positive pedagogical atmospheres and supportive supervisory relationships substantially enhance nursing students’ clinical learning. These human factors may help offset systemic and geopolitical barriers. Findings support targeted efforts in faculty development, clinical teaching strategies, and institutional coordination to build educational resilience.